The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms221910547
|View full text |Cite
|
Sign up to set email alerts
|

Organoids: An Emerging Tool to Study Aging Signature across Human Tissues. Modeling Aging with Patient-Derived Organoids

Abstract: The biology of aging is focused on the identification of novel pathways that regulate the underlying processes of aging to develop interventions aimed at delaying the onset and progression of chronic diseases to extend lifespan. However, the research on the aging field has been conducted mainly in animal models, yeast, Caenorhabditis elegans, and cell cultures. Thus, it is unclear to what extent this knowledge is transferable to humans since they might not reflect the complexity of aging in people. An organoid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…These challenges lead researchers to study senescent cells in vitro ( González-Gualda et al, 2021 ) however, as discussed above, 2D cell cultures do not reflect the true representation of human aging. Very recently, researchers have been focused on more advanced methods to study senescence and one of the most promising techniques to study CS is proposed as 3D organoid cultures ( Torrens-Mas et al, 2021 ). Organoid systems are simplified organs developed to model many human tissues and diseases ( Hu et al, 2018 ), reconstructing physiological 3D tissue structure and cellular composition in vitro ( Simian and Bissell, 2017 ).…”
Section: The Tools Of Cellular Senescence Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…These challenges lead researchers to study senescent cells in vitro ( González-Gualda et al, 2021 ) however, as discussed above, 2D cell cultures do not reflect the true representation of human aging. Very recently, researchers have been focused on more advanced methods to study senescence and one of the most promising techniques to study CS is proposed as 3D organoid cultures ( Torrens-Mas et al, 2021 ). Organoid systems are simplified organs developed to model many human tissues and diseases ( Hu et al, 2018 ), reconstructing physiological 3D tissue structure and cellular composition in vitro ( Simian and Bissell, 2017 ).…”
Section: The Tools Of Cellular Senescence Researchmentioning
confidence: 99%
“…Since organoids have the ability to histologically recapitulate human tissues in vivo , this technology holds the potential to test potential longevity drugs that target the hallmarks of aging including CS, while paving the way to personalized interventions. However, organoid cultures also lack some physiological features of the organisms such as vascularization and further developments are needed to better represent the physiology of human aging ( Torrens-Mas et al, 2021 ).…”
Section: The Tools Of Cellular Senescence Researchmentioning
confidence: 99%
“…Telomere shortening is also a hallmark of the aged intestine and predisposes to age-related intestinal disease. While studies in organoids derived from the elderly have shown reduced formation efficiency 85 , indicative of a stem cell compromise, the effect of telomere shortening on differentiation and function of the intestine is not known. In particular, a region-specific analysis would be important, as heterogeneity in telomere length is observed in the intestine, including shorter telomeres in neoblastic adenomas that are invariably characterized by inflammation 86 .…”
Section: Discussionmentioning
confidence: 99%
“…However, brain organoids resemble the prenatal brain, which limits the ability of these organoids to model the mature brain ( 143 ). Therefore, developing reliable strategies to age brain organoids will be crucial for studying ageing-related disorders such as AD and PD ( 144 , 145 ).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%